2022
DOI: 10.3389/fnins.2022.933290
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Herbal Medicine for Functional Dyspepsia With Psychological Disorders: A Systematic Review and Meta-Analysis

Abstract: Background and AimsFunctional dyspepsia (FD) is closely associated with gut–brain interaction disorder (DGBI), characterized by the interaction of gastrointestinal symptoms and central nervous system dysregulation. Chinese herbal medicine (CHM) has a good concurrent effect in the treatment of FD, especially for patients with concurrent psychological disorders. A meta-analysis was designed to evaluate the efficacy and safety of CHMs in the treatment of FD.MethodsThe PubMed, Embase, Cochrane Library, Web of Scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…This study presents the first systematic meta-analysis that evaluates the efficacy of acupuncture in treating FD accompanied by symptoms of depression and anxiety. Although previous meta-analyses have confirmed the effectiveness of Chinese Herbal Medicine in traditional Chinese medicine for treating FD with psychological conditions [ 47 ], no comparable systematic evaluations exist for acupuncture. To bridge this gap, we used various validated scales to measure the severity of depression and anxiety in patients.…”
Section: Discussionmentioning
confidence: 99%
“…This study presents the first systematic meta-analysis that evaluates the efficacy of acupuncture in treating FD accompanied by symptoms of depression and anxiety. Although previous meta-analyses have confirmed the effectiveness of Chinese Herbal Medicine in traditional Chinese medicine for treating FD with psychological conditions [ 47 ], no comparable systematic evaluations exist for acupuncture. To bridge this gap, we used various validated scales to measure the severity of depression and anxiety in patients.…”
Section: Discussionmentioning
confidence: 99%
“…When individuals experience FGIDs, they tend to also experience anxiety reactions. This is so recurrent that it is challenging to stop the cycle of problems between psychological and physical disorders[ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a form of reciprocity, studies have shown that the incidence of psychological disorders in patients with FGIDs is significantly higher than in non-FGID patients; symptoms of FGIDs are strongly associated with mental health disorders, especially anxiety and depression [ 49 , 50 ]. Pathophysiological studies of FGIDs have shown that psychosocial factors can influence FGIDs by regulating processing pathways and decreasing visceral signaling in the brain [ 29 , 32 ]. Analyses of interventions for irritable bowel syndrome have shown that psychological interventions, including web-based CBT, could treat irritable bowel syndrome effectively in patients [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chinese herbal medicine (CHM) has a long history and rich experience in CG treatment. CHM can regulate the functions of the stomach and spleen, harmonize the liver and stomach, eliminate dampness and heat, promote blood circulation, and eliminate blood stasis[ 6 ]. CHM can also modulate the immune system, inhibit the growth of H. pylori , protect the gastric mucosa, and improve the quality of life of patients with CG[ 7 ].…”
Section: Introductionmentioning
confidence: 99%